A diaconia da visitação a pessoas doentes em comunidade eclesial urbana - Knop, Silvia Prade (2010)
The purpose of this dissertati on is to investigate the neces sity and the importance of diaconal visitation to ill people in an urban context. Besides that, it has the objective of researching the creation of teams of visitors in order to assist the members needs and expectations at their homes, hospitals, medical clinics and communities. The first chapter displays the Social Research, its analysis and its respective results. The second chapter presents the comprehension of diakonia terminology and the concept of diakonia and visitation from a biblical and theologica l research based on some evangelists texts such as: Marcos 10.35-45, Mateus 25.42-44, João 13.1-15, and Lucas 22.24-30. It also brings out a resea rch concerning community diakonia, diakonia and visitation, and visitation as a service in the community. The third chapter presents some suggestions for the practice of visitation to ill people in an urban community. The research concludes that ill people in an urban ecclesiastic community need to be visited. Visitation provides reconciliation, cure and the faith strength on suffering.